Analisis pengendalian biaya produksi dalam meningkatkan laba Pada PT. Ferdinand Mandiri - Ratih Anggraini Siregar; Purwita Sari; Widya Astuti; Gita Ramadhani (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
This study aims to determine the obstacles and efforts faced at PT. Ferdinand Mandiri in carrying out its operational activities to support profit effectiveness. The method used in this study is a descriptive research method with a qualitative approach, where the researcher collects data, then analyses the data and concluded based on the facts at the time of the research. The results of the study concluded that the production costs paid by PT. Ferdinand Mandiri experienced an increase from 2019-2021, but the profits generated fluctuated and tended to decline in 2021. The effectiveness of a company's profits is measured by the extent to which the company is able to realize the goals that have been set or planned in advance.